Molecular detection of Haemoparasitic Babesia spp. infection in Thai flighting bulls in Nakhon Si Thammarat province, Thailand - Kompan, Jaturapat; Khophlolklang, Vassakorn; Thiptara, Anyarat; Kongkaew, Wandee; Sirisriro ์Nijjareeya (Recent Science and Technology, 2025)
Bovine babesiosis significantly impacts cattle health and productivity; however, its epidemiology in Thai fighting bulls remains understudied. This research investigated the prevalence and genetic characteristics of Babesia species in these bulls from Nakhon Si Thammarat province, Thailand. Blood samples from 267 bulls across 13 districts were analyzed using PCR targeting the ama-1 gene. The overall Babesia prevalence was 12.36%. District-specific infection rates were: Nophitam, 20.0% (4/20); Phipun, 15.0% (3/20); Ronphibun, 31.81% (7/22); Chulaphon, 15.0% (3/20); Chauat, 25.0% (5/20); Huasai, 25.0% (5/20); and, Chianyai, 26.09% (6/23). Sequencing identified Babesia bovis as the sole infecting species; B. bigemina was not detected. Nucleotide sequencing confirmed that all positive samples were Babesia bovis, and B. bigemina was not detected. Phylogenetic analysis of the B. bovis ama-1 sequences delineated two distinct genetic clades with geographical correlation. Clade I, comprising isolates from the northern districts of Nophitam and Phipun, exhibited close genetic relatedness to isolates from Brazil and other regions of Thailand. Conversely, Clade II, encompassing isolates from the southern districts of Ronphibun, Chulaphon, Chauat, Huasai, and Chianyai, showed genetic similarity to isolates from Israel and Sri Lanka. The varying district prevalence highlights heterogeneous infection distribution, indicating high-risk areas for targeted interventions. Distinct phylogenetic clades suggest regional B. bovis strain differences, warranting further investigation into transmission and management implications for this economically and culturally important fighting bull population.